Whole genome typing of the recently emerged Canadian serogroup W Neisseria meningitidis sequence type 11 clonal complex isolates associated with invasive meningococcal disease. (April 2018) - Tsang, Raymond S.W.; Ahmad, Tauqeer; Tyler, Shaun; Lefebvre, Brigitte; Deeks, Shelley L.; Gilca, Rodica; Hoang, Linda; Tyrrell, Gregory; Van Caeseele, Paul; Van Domselaar, Gary; Jamieson, Frances B.
Abstract: Objectives: This study was performed to analyze the Canadian invasive serogroup W Neisseria meningitidis (MenW) sequence type 11 (ST-11) clonal complex (CC) isolates by whole genome typing and to compare Canadian isolates with similar isolates from elsewhere. Methods: Whole genome typing of 30 MenW ST-11 CC, 20 meningococcal group C (MenC) ST-11 CC, and 31 MenW ST-22 CC isolates was performed on the Bacterial Isolate Genome Sequence database platform. Canadian MenW ST-11 CC isolates were compared with the 2000 MenW Hajj outbreak strain, as well as with MenW ST-11 CC from other countries. Results: Whole genome typing showed that the Canadian MenW ST-11 CC isolates were distinct from the traditional MenW ST-22 CC; they were not capsule-switched contemporary MenC strains that incorporated MenW capsules. While some recent MenW disease cases in Canada were caused by MenW ST-11 CC isolates showing relatedness to the 2000 MenW Hajj strain, many were non-Hajj isolates similar to current MenW ST-11 isolates found globally. Geographical and temporal variations in genotypes and surface protein antigen genes were found among the MenW ST-11 CC isolates. Conclusions: The current MenW ST-11 isolates did not arise by capsule switching from contemporary MenC ST-11 isolates. Both the Hajj-related and non-Hajj MenW ST-11 CC strains were associated with invasive meningococcal disease in Canada.